Antimicrobial susceptibility profiles of anaerobic bacteria, isolated from human clinical specimens, within different European and surrounding countries. A joint ESGAI study. (February 2020) - Veloo, A.C.M.; Tokman, H. Bahar; Jean-Pierre, H.; Dumont, Y.; Jeverica, S.; Lienhard, R.; Novak, A.; Rodloff, A.; Rotimi, V.; Wybo, I.; Nagy, E.; ,
Abstract: Objectives: Studies on the antimicrobial susceptibility profile of anaerobic bacteria are underrepresented in the literature. Within this study we aim to give an extensive overview of the differences in antimicrobial susceptibility profiles between different European and surrounding countries. Methods: Minimal inhibitory concentration (MIC) data of different antibiotics were collected from 10 participating laboratories, representing an equal number of countries. All MIC's were determined using Etest, according to the protocol used by the participating laboratory. Anaerobic genera represented by at least 10 clinical isolates were included in the study. Results: Each country tested different antibiotics, sometimes depending on the kind of infection and/or the anaerobic species isolated. All countries tested clindamycin and metronidazole. Resistance rates differed remarkably between the different countries. Especially in Kuwait, resistance was high for all tested antibiotics. Unexpected metronidazole resistance was observed for Finegoldia magna isolates, Peptoniphilus isolates and Eggerthella lenta isolates. Conclusions: Due to the extensive differences in antimicrobial susceptibility profile of anaerobic bacteria isolated within different countries, we strongly recommend to perform this kind of study on a regular basis. Highlights: Antimicrobial susceptibility profiles of anaerobes from different countries. Unexpected antimicrobial susceptibility profiles were encountered. Extensive differences between countries was observed. Recommend to perform this kind of study on a regular basis.